Technical Quality of Maternity Care: the Pregnant Women’s Perspective - Mostafa Farahbakhsh; Kamal Gholipour; Jafar Sadegh Tabrizi; Andrew Wilson (Health Promotion Perspectives, 2013)
Background: Improving adherence to care standards is one way to im¬prove quality of delivered care. This study aimed to determine the degree of provid¬ers' adherence to maternity care standards from the perspective of pregnant women.Methods: This cross-sectional study was conducted on 185 pregnant women in their ninth month of pregnancy who received maternity care from health centres in Tabriz, Iran. Participants were selected randomly from 40 health centres. Data collection used a researcher-developed ques¬tionnaire based on Iranian Ministry of Health (MOH) standards for mater¬nity care. Question¬naire validity was reviewed and confirmed by 10 experts.Results: About 69% of pregnant mothers during their 9-month pregnancy received at least six items of standard maternity care. Almost two-thirds of participants received recommended maternity care at or above minimal standards for some aspect, such as the number of care during pregnancy, referral to health centre physician, and weight and blood pressure measure¬ment. Some other services such as measuring uterus height, review for oedema and varicosities, referral to a dentist, listening for fetal heart sound and vaginal examination, were reported at very low adherence to the Ministry of Health guidelinesConclusion: A notable proportion of pregnant mothers reported receiving subop-timal care indicating significant room for improving the quality of maternity care based on Iranian MOH standards and guidelines. The results indicate potential benefits from interventions to improve health care provid¬ers training and the awareness of pregnant women about the standards for good maternity care.